The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s12015-022-10425-w
|View full text |Cite
|
Sign up to set email alerts
|

PBX1-SIRT1 Positive Feedback Loop Attenuates ROS-Mediated HF-MSC Senescence and Apoptosis

Abstract: Stem cell senescence and depletion are major causes of aging and aging-related diseases. The NAD (Nicotinamide adenine dinucleotide) – SIRT1 (Silent Information Regulator 1) – PARP1 (Poly (ADP-ribose) polymerase-1) axis has gained interest owing to its significant role in regulating stem cell senescence and organismal aging. A recent study from our lab showed that pre-B-cell leukemia transcription factor1 (PBX1) overexpression attenuates hair follicle-derived mesenchymal stem cells (HF-MSCs) senescence and apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 37 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…PBX1 rescued ATP and NAD depletion mediated by PARP1 overexpression, accompanied by increased SIRT1 expression. This highlights a critical role of the PBX1-SIRT1-PARP1 axis in alleviating senescence and apoptosis in HF-MSCs 61 .…”
Section: Pbx1 Structure Development and Function In Regenerative Medi...mentioning
confidence: 85%
“…PBX1 rescued ATP and NAD depletion mediated by PARP1 overexpression, accompanied by increased SIRT1 expression. This highlights a critical role of the PBX1-SIRT1-PARP1 axis in alleviating senescence and apoptosis in HF-MSCs 61 .…”
Section: Pbx1 Structure Development and Function In Regenerative Medi...mentioning
confidence: 85%
“…Using molecular docking simulations and cell-based studies, we herein demonstrated that both 4-dmH and heliomycin targeted SIRT1 and inhibited its activity and expression, to attenuate the growth of oral cancer cells. Given that SIRT1 contributes to a complex regulatory network, it is of primary importance to understand the fundamental regulatory mechanisms of SIRT1 in cell death regulation ( Wang et al, 2023 ; Wang et al, 2021a ; Lee et al, 2018 ; Zhu et al, 2020 ; Ran et al, 2023 ; Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pbx1 mRNA produces two transcripts, Pbx1a and 1b, during variable splicing; and Pbx1 is commonly expressed in embryonic and adult tissues [ 19 ]. Intriguingly, it was shown that enhanced expression of a Pbx1-Sirt1 positive-feedback loop significantly attenuated ROS-induced senescence and apoptosis in hair follicle-derived mesenchymal stem cells [ 26 ], suggesting that Pbx1 expression was negatively correlated with senescence. The above reports are in close agreement with our experimental results and indirectly support our findings and scientific hypotheses.…”
Section: Discussionmentioning
confidence: 99%